Evaluation of the Arjun’s Royal Air Force Device as a New Tool for Assessing Near Point of Convergence and Near Point of Accommodation - Ankit Sanjay Varshney; Sanjay Mehta; Chetna Suresh Patel; Mahendrasinh D. Chauhan (Delhi Journal of Ophthalmology)
Context: The Arjun’s Royal Air Force (ARAF) device is a newly developed digital tool designed to assess near point of convergence (NPC) and near point of accommodation (NPA). It aims to address the limitations of the traditional Royal Air Force (RAF) rule by enhancing precision, comfort, and clinical usability. Aims: This aims to evaluate the accuracy, efficacy, and user satisfaction of the ARAF device compared to the RAF rule in assessing NPC and NPA. Settings and Design: A prospective observational study was conducted at a tertiary eye care center, involving 56 participants with a mean age of 21.55 ± 5.36 years. Subjects and Methods: Participants underwent NPC and NPA assessments using both the ARAF device and the RAF rule. The order of device usage was randomized, with three trials per device for each participant. Subjective feedback on comfort and usability was collected using a structured questionnaire. Statistical Analysis Used: The Wilcoxon signed-rank test was used for statistical comparison, with significance set at P < 0.05. Results: The ARAF device demonstrated statistically significant improvements in measurement precision for NPC (P = 0.004) and NPA (monocular: P <0.01; binocular: P = 0.003) compared to the RAF rule. Effect sizes indicated a moderate impact favoring the ARAF device. Subjective feedback showed that 53.57% of participants rated the ARAF device as more comfortable and user-friendly, highlighting its ergonomic design and automated digital readout as advantages. Preference for the RAF rule was limited to 28.57%, while 17.85% expressed no preference. Conclusions: The ARAF device provides a precise, reliable, and user-friendly alternative to the RAF rule for NPC and NPA assessments. Its automation enhances diagnostic accuracy, reduces examiner fatigue, and improves patient comfort, making it valuable for high-throughput clinical settings and in pediatric or geriatric care. Further studies with diverse populations are recommended to validate these findings.